Modelling effect of sericitization of plagioclase on the 40K/40Ar and 40Ar/39Ar chronometers: implication for dating basaltic rocks and mineral deposits - Verati, C.; Jourdan, Fred (Geological Society Publishing House, 2013)
The 40Ar/39Ar technique is the most commonly used technique to date basaltic rocks. For basaltic rocks older than about 30 Ma, the dating of plagioclase separates is preferred over groundmass as the latter is susceptible to containing cryptic alteration due to fluid circulations, difficult if not impossible to remove during sample preparation. Alteration under such metamorphic conditions progressively forms K-rich sericite after plagioclase. Owing to its transparency, plagioclase allows a distinction to be made optically between partially–completely altered grains and fresh grains. However, practice shows that grains that contain less than about 1% of sericite are hard to identify under the stereomicroscope. Owing to the high K2O content (c. 10 wt%) of sericite, such compromised grains can have dramatic effects on the age determination of plagioclase.Here, we investigate and quantify the effect of sericite on the 40Ar/39Ar age determination of plagioclase using a numerical model with multiple variable parameters. We show that the most influential parameter is the time difference between the crystallization of plagioclase and the sericitization event. We also show that for some continental flood basalts, even 0.1 wt% of sericite can bias the apparent age of a plagioclase separate by several hundred thousand years. The presence of sericite can be identified using a combination of Ca/K ratios, age spectra, and 39Ar and 37Ar degassing curves obtained during a conventional 40Ar/39Ar step-heating procedure. When the age of the fresh plagioclase and its Ca/K ratio are known, the percentage of sericitization and the age of the alteration event can be estimated. Ultimately, above approximately 65% of sericitization, the apparent age measured on the altered plagioclase is within ±1% of the age of the alteration event, with implications for accurately dating low-temperature metamorphism and mineral deposit formations.